Numerical study on load-bearing capabilities of beam-like lattice structures with three different unit cells - Niu, Jie; Choo, Hui Leng; Sun, Wei; Mok, Sui Him (Springer, 2017)
The design and analysis of lattice structures manufactured using Additive Manufacturing (AM) technique is a new approach to create lightweight high-strength components. However, it is difficult for engineers to choose the proper unit cell for a certain function structure and loading case. In this paper, three beam-like lattice structures with triangular prism, square prism and hexagonal prism were designed, manufactured by SLM process using AlSi10Mg and tested. The mechanical performances of lattice structures with equal relative density, equal base area and height, and equal length for all unit cells were conducted by Finite Element Analysis (FEA). It was found that effective Young’s modulus is proportional to relative density, but with different affecting levels. When the lattice structures are designed with the same relative density or the same side lengths, the effective Young’s modulus of lattice structure with triangular prism exhibits the maximum value for both cases. When the lattice structures are designed with the same base areas for all unit cells, the effective Young’s modulus of lattice structures with square prism presents the maximum. FEA results also show that the maximum stress of lattice structures with triangular prisms in each comparison is at the lowest level and the stiffness-to-mass ratio remains at the maximum value, showing the overwhelming advantages in terms of mechanical strength. The excellent agreements between numerical results and experimental tests reveal the validity of FEA methods applied. The results in this work provide an explicit guideline to fabricate beam-like lattice structures with the best tensile and bending capabilities.